Comparative economic analysis of dairy characteristics focused on repeat breeding losses in selected milk pocket areas of Bangladesh - Islam, MN; Bari, MS; Habib, MR; Sarkar, MM; Islam, MA (Bangladesh Journal of Animal Science, 2020)
Dairy farming is an important approach for farmers to increase their incomes and which has a significant contribution to the economy of Bangladesh. The present study describes the dairy characteristics and estimates the financial profitability of dairy farming in selected milk pocket districts of Bangladesh. Following study areas- Sirajganj, Bogura, Rangpur, Satkhira and Munshiganj districts were selected based on the fastest growing dairying, abundant number of dairy farms and contribution in national milk production. Two hundred and sixty-five (265) dairy farms were selected across the study areas and data were collected through direct interview method. The study revealed that dairy herd sizes from the surveyed farms varied from 5 to 19 per farm. Average milk productivity was found 7 to 10 L per cow per day, in which Satkhira district cow’s milk productivity per day (10 L/cow/d) and lactation (3,116 L/cow/lactation) was found the highest and Rangpur district was the lowest. On the contrary, significantly (p=0.000) highest milk production per farm per lactation was in the Rangpur district (33,697 L) and the lowest in the Bogura district (9,818 L). Results revealed that statistically (p=0.000) higher income generated in Munshiganj district in terms of per cow per year and/or per day compared to the other milk pocket districts. The study also indicated that repeat breeding cost and unavailable income per farm per year were higher in the Sirajganj district and lowers in the Bogura district. Repeat breeding problems increases the production cost of the animals significantly (p=0.000) and negatively affect the farm profitability of the milk pocket areas in Bangladesh. Annually gross margin and net return per cow were statistically (p=0.000) higher in Munshiganj district. Benefit-cost ratios were found more than one and indicated that benefit is much higher than the cost of production at Satkhira (annual BCR/farm=1.52) and Munshiganj districts (annual BCR/farm=1.50) compared to the other areas (0.27–0.35 units more). Dairy farming provides higher economic benefits to the farmers of Munshiganj and Satkhira districts compared to the other milk pocket districts. The research concludes that there is an ample scope and possibility for sustaining and developing dairy farming in the milk pocket districts of Bangladesh. Overall, it may be suggested that the causes of repeat breeding should be identified and corrected accordingly within the shortest possible time for the betterment of dairying. Also, milk prices should be similar across the milk pocket districts and essential inputs prices should be kept within the affordable purchase range of farmers for sustainable dairying. Bang. J. Anim. Sci. 2019. 48 (2): 145-154